Evaluating reproduction traits in a crossbreeding program between indigenous and exotic sheep in semi-arid lands - Oyieng, Edwin P.; Ojango, Julie M.K.; Gauly, M.; Mrode, Raphael A.; Dooso, Richard; Okeyo Mwai, Ally; Kalinda, C.; König, S. (Elsevier, 2025)
Reproduction traits are important factors determining the efficiency of any sheep production system. This study evaluates the age at first lambing (AFL), lambing interval (LI), litter weight at birth (LBWT), litter weight at weaning (LWWT), birth weight of ewe (EBWT) and weaning weight of ewes (EWWT) in a crossbreeding program between the Red Maasai (RRRR) and Dorper sheep and their crosses, 75% Dorper and 50% Dorper (DDRR) breeds. All the traits significantly (P < 0.05) differed across breeds and season of birth of the ewe. LBWT and LWWT were significantly affected by the sex of the lamb, type of birth of the lamb and parity in which the lambs were born in. AFL and LI had very high environmental variances. Overall heritability estimates of AFL (0.09 ± 0.04) and LI (0.00 ± 0.01) were not significant from zero while the heritability estimates for EBWT (0.38 ± 0.04), EWWT (0.23 ± 0.03), LBWT (0.19 ± 0.03) and LWWT (0.09 ± 0.02) were significant (P < 0.05). The RRRR had the highest genetic gain for all traits while the DDRR had a higher genetic gain among the crosses. LI had negative genetic correlations with LBWT (−0.53 ± 0.08) and LWWT (−0.28 ± 19.59) while AFL had positive genetic correlations with LBWT (0.27 ± 0.46) and LWWT (0.31 ± 0.34). The phenotypic trends for AFL and LWWT showed a negative and positive association, respectively, with the rainfall index over the years. With proper farm management, improved reproduction performance of ewes is possible by indirect selection using LBWT and LWWT for the Red Maasai, Dorper and their crosses within the semi-arid lands.